2022
DOI: 10.3389/fnut.2022.814269
|View full text |Cite
|
Sign up to set email alerts
|

Gut Dysbiosis in Pancreatic Diseases: A Causative Factor and a Novel Therapeutic Target

Abstract: Pancreatic-related disorders such as pancreatitis, pancreatic cancer, and type 1 diabetes mellitus (T1DM) impose a substantial challenge to human health and wellbeing. Even though our understanding of the initiation and progression of pancreatic diseases has broadened over time, no effective therapeutics is yet available for these disorders. Mounting evidence suggests that gut dysbiosis is closely related to human health and disease, and pancreatic diseases are no exception. Now much effort is under way to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
10

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 239 publications
0
26
0
10
Order By: Relevance
“…There is evidence of the association between gut microbiota and cancer initiation, progression, treatment response, and side effects. 11 , 12 , 13 , 14 , 24 , 25 The gut microbiota modulates the host immune system, interacts with host metabolism, and produces toxins and metabolites which influence the tumor microenvironment. 26 However, few studies have investigated the effects of intravenous administration of chemotherapy drugs on the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is evidence of the association between gut microbiota and cancer initiation, progression, treatment response, and side effects. 11 , 12 , 13 , 14 , 24 , 25 The gut microbiota modulates the host immune system, interacts with host metabolism, and produces toxins and metabolites which influence the tumor microenvironment. 26 However, few studies have investigated the effects of intravenous administration of chemotherapy drugs on the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…Meta‐analyses and systematic reviews have revealed that gut dysbiosis is closely related to human health, chemotherapy‐related side effects, and surgery‐related complications and diseases 12–14 . In this study, we investigated the effects of systemic chemotherapy with GC on the gut microbiome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…211 Studies have shown that most pancreatic and extra-pancreatic organ infections originate in the intestine and induce inflammatory responses, which are major causes of 'secondary attack' and increased late death of patients with SAP. 212 Changes in the GM play an important role in intestinal homeostasis and aggravate the inflammatory response under intestinal 190 Wang et al, 199,200 Zhang et al 201 Six different strains of probiotic prophylaxis mixture More multiorgan failure-related deaths…”
Section: Therapeutic Advances In Gastroenterologymentioning
confidence: 99%
“…Additionally, it is worth noticing that multiple factors can contribute to the development and severity of both diabetes and COVID-19. For instance, disturbances in gut microbiome composition and gut permeability might underlie a low-grade inflammation, which has been linked to new-onset diabetes ( Alkanani et al, 2015 ; Leiva-Gea et al, 2018 ; Zhang et al, 2022 ) and to the increased severity and mortality of COVID-19 ( Giron et al, 2021 ; Giannos and Prokopidis, 2022 ; Schult et al, 2022 ). Similarly, diabetes and SARS-CoV-2 infection both trigger pro-inflammatory reactions independently.…”
Section: Pancreatitis and New-onset Diabetes As Complications After S...mentioning
confidence: 99%